Investigate the Potential Renewable Energy of Microalgae Spirulina sp Using Proximate Analyzer, SEM-EDX, and Thermogravimetry - Zakaria, Yahya; Sukarni, Sukarni; Puspitasari, Poppy; Mufti, Nandang; Anis, Samsudin; Johari, Anwar (Universitas Negeri Malang, 2022)
Microalgae Spirulina sp which has been cultivated by the Brackishwater Aquaculture Development Center, Situbondo Indonesia were tested for their potential energy performance using proximate analyzer, SEM-EDX, and thermogravimetry. The proximate analyzer showed volatile matter (VM), fixed carbon (FC), moisture, ash content (AC), total sulfur of microalgae Spirulina sp 68.15, 12.57, 11.22, 8.06, and 0.67 (wt%, ar), respectively, and the gross calorific value (GCV) is 4971 kcal/kg (dry basis). SEM-EDX test showed the morphology and chemical content of Spirulina sp. The content of microalgae Spirulina sp is dominated by carbon (C) and oxygen (O), then followed by chlorine (Cl), sodium (Na), potassium (K), sulfur (S), magnesium (Mg), and phosphorus (P). Thermogravimetry pyrolysis test of microalgae Spirulina sp resulted thermogravimetry (TG) analysis and derivative thermogravimetry (DTG) analysis curve, which is divided into three different steps. The moisture of microalga Spirulina sp was vaporized at the first step, started at 27°C, and finished at 173°C with a decomposed mass of about 13.81% of the total initial mass. The second step began at the end of vaporize moisture at about 173°C and ended at around 618 °C. The gasification process occurred in volatile matter content and resulted mass loss of about 57.9% of Spirulina sp total mass. The last step showed the process of gasification of residual substances, started at the end of the volatile matter step, 618°C, and stopped at 995°C with a decomposed mass of 24.6% from total mass.